2016
DOI: 10.1016/j.parkreldis.2016.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime occupational and leisure time physical activity and risk of Parkinson's disease

Abstract: Introduction While regular exercise has been shown to alleviate the motor symptoms of Parkinson’s disease (PD), it remains unclear whether a physically active lifestyle may prevent PD. Methods To examine physical activities across the lifespan and risk of PD, we relied on data from a population-based case-control study that enrolled 357 incident PD cases and 341 controls. We assessed physical activity levels via self-report of (1) overall physical activity (PA) over 4 age periods; (2) competitive sports; and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 29 publications
3
43
1
Order By: Relevance
“…A Canadian report was released stating that white-collar workers were more motivated to participate in sports or physical recreation for health reasons, enjoyment, and so forth, and that blue-collar workers were satisfied with their present exercise levels and had less awareness of the health benefits of physical activity [32]. LTPA has been shown to be associated with better health [712,15,2931]. The demographic groups that are more likely to experience poorer health tend to be those used in blue-collar jobs [24–27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A Canadian report was released stating that white-collar workers were more motivated to participate in sports or physical recreation for health reasons, enjoyment, and so forth, and that blue-collar workers were satisfied with their present exercise levels and had less awareness of the health benefits of physical activity [32]. LTPA has been shown to be associated with better health [712,15,2931]. The demographic groups that are more likely to experience poorer health tend to be those used in blue-collar jobs [24–27].…”
Section: Discussionmentioning
confidence: 99%
“…One study showed that although overall and leisure-time physical activity were associated with Parkinson’s disease, occupational physical activity was not [7]. A few European studies found that moderate and high LTPA reduced the risk of cardiovascular disease and mortality, whereas occupational physical activity had opposite results [810].…”
Section: Introductionmentioning
confidence: 99%
“…A beneficial relationship between physical activity and PD was first suggested in 1992, when Sasco and colleagues reported that the future risk of PD was reduced in men who played sports in college and adult life and that PD risk was increasingly lower as activity levels increased . This finding has been replicated in nearly all subsequent epidemiologic studies (Table ). For example, among the more than 200,000 participants in the NIH‐AARP Diet and Health Study cohort, those who participated in consistent and frequent moderate to vigorous activities had a 40% lower risk of developing PD compared with sedentary participants.…”
Section: Physical Activity Exercise and Reduction Of Parkinson's DImentioning
confidence: 91%
“…1 case‐control study performed in the USA showed that physical activity was associated with reduced risk for PD: OR 0.50 to 0.64 depending on the age in which the person engaged in physical activity …”
Section: Analytical Epidemiologymentioning
confidence: 99%